2010
DOI: 10.1016/j.cmet.2010.11.008
|View full text |Cite|
|
Sign up to set email alerts
|

Total Skeletal Muscle PGC-1 Deficiency Uncouples Mitochondrial Derangements from Fiber Type Determination and Insulin Sensitivity

Abstract: SUMMARY Evidence is emerging that the PGC-1 coactivators serve a critical role in skeletal muscle metabolism, function, and disease. Mice with total PGC-1 deficiency in skeletal muscle (PGC-1α−/−βf/f/MLC-Cre mice) were generated and characterized. PGC-1α−/−βf/f/MLC-Cre mice exhibit a dramatic reduction in exercise performance compared to single PGC-1α- or PGC-1β-deficient mice and wild-type controls. The exercise phenotype of the PGC-1α−/−βf/f/MLC-Cre mice was associated with a marked diminution in muscle resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
173
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(191 citation statements)
references
References 46 publications
18
173
0
Order By: Relevance
“…Whether these transient modifications of PGC-1␣ have an impact on RSV-mediated mitochondrial biogenesis remains to be determined. There is also considerable contention as to whether PGC-1␣ acts as a sole regulator of the induction of organelle synthesis in muscle, at least in response to exercise (20,(53)(54)(55). Thus, this raises the possibility that RSV may act through other mediators of mitochondrial biogenesis such as PGC-␤ or PGC-1␣-related coactivator.…”
Section: Sirt1-mediated Effects On Mitochondrial Biogenesismentioning
confidence: 95%
“…Whether these transient modifications of PGC-1␣ have an impact on RSV-mediated mitochondrial biogenesis remains to be determined. There is also considerable contention as to whether PGC-1␣ acts as a sole regulator of the induction of organelle synthesis in muscle, at least in response to exercise (20,(53)(54)(55). Thus, this raises the possibility that RSV may act through other mediators of mitochondrial biogenesis such as PGC-␤ or PGC-1␣-related coactivator.…”
Section: Sirt1-mediated Effects On Mitochondrial Biogenesismentioning
confidence: 95%
“…The role of dysfunctional mitochondria in the development of type 2 diabetes has been highly controversial because mitochondrial dysfunction leads to the protection against obesity and insulin resistance in apoptosis-inducing factor 1 (AIF1)-, mitochondrial transcription factor A (TFAM)-, or PGC-1␣/␤-deficient mice (32,33,57). However, our data showed that CI dysfunction resulted in a decrease of the NAD ϩ /NADH ratio, the deactivation of SIRT1, an increased expression level of PTP1B, the inactivation of IR␤ and IRS-1, and insulin resistance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, this proposal has been challenged because the expression levels of the OXPHOS proteins are similar in the skeletal muscles of lean and db/db mice, and OXPHOS function is similar in diabetic and nondiabetic Asian Indians (28 -30). In addition, disruption of mitochondrial transcription factor A (TFAM), apoptosis-inducing factor, or PGC-1␣ and PGC-1␤␤ improves glucose tolerance and increases insulin sensitivity despite severe CI activity loss and mitochondrial defects (31)(32)(33).…”
mentioning
confidence: 99%
“…Nevertheless, when overexpressed in skeletal muscle, genes involved in oxidative phosphorylation and fatty acid oxidation are also upregulated by PGC-1β resulting structurally in a higher mitochondrial density and functionally in a better endurance performance [89]. Inversely, skeletal muscle-specific PGC-1 deletion causes lower endurance capacity [106]. A combined deficiency of PGC-1 and PGC-1 in a global PGC-1α and a musclespecific PGC-1β knockout background aggravates this phenotype displaying a very severe exercise deficit, strongly reduced oxidative capacity and mitochondrial structure and function derangements.…”
Section: Role Of Pgc-1 Coactivators In Oxidative Metabolism and Skelementioning
confidence: 99%